AMYLOLYTIC POTENTIAL OF Arthrobacter sp. AND Bacillus aerius FROM WASTE DUMP-SITES OF TWO BAKERIES LOCATED WITHIN KADUNA METROPOLIS, NIGERIA - Obafunmi, Tonidunni Ibukunola; Bakori, Garba Faiza; Lawal, Yunus Sumayya (FUDMA JOURNAL OF SCIENCES, 2023)
Bakery waste dumpsites are believed to harbour a variety of bacteria due to the presence of organic materials like flour, sugar, and other food residues. The conditions in these environments support the growth of bacteria with the ability to degrade starch into simple sugars because they produce amylases, an enzyme pivotal to the food and beverage production. As Amylases progressively gain relevance in several other starch-based processes, their availability becomes insufficient, and the need for amylases with unique and superior efficiency increases. The focus of this study was to isolate and characterize bacteria with amylase activity from the soil of bakery waste dumpsites to provide valuable insight into cheap sources of amylolytic bacteria and their potential biotechnological applications. The starch-agar medium was used to isolate and screen amylase-producing bacteria by streak plate method. Two isolates, A2 and A4, showing the most hydrolytic activities of 21 + 0.1 mm and 25 + 0.1 mm, respectively, were identified by their cultural and cellular morphologies, biochemical characteristics, 16S rRNA gene sequence, and nearest phylogenetic neighbour as Arthrobacter sp. and Bacillus aerius. Based on their culture and amylolytic temperatures, Arthrobacter sp. (37 0C) and Bacillus aerius (45 0C) tend to produce amylases that can be explored in low to moderate and moderate to torrid industrial processes, respectively.